Articulate Storyline-Based Learning Media Loaded with Local Wisdom Values in Historical Narrative Text Material for Elementary School Students - Konradus Silvester Jenahut; Angelina Christin O. Rosari Lake (Jurnal Ilmiah Sekolah Dasar, 2023)
Many elementary school students still need help understanding historical narrative text material given by teachers at school. This study aimed to develop an Articulate Storyline-based learning media containing local wisdom values in historical narrative text material for fifth-grade elementary school students. This type of research is development research, which refers to the development model of the Borg & Gall model. Data collection methods in this study are in the form of observation, interviews, and questionnaires. The data analysis of this research was carried out in a descriptive qualitative and quantitative descriptive manner. The subjects of this product trial were three teachers and 58 students from 3 elementary schools selected using purposive random sampling. Based on the results of the validation, learning media experts provide an assessment with an average percentage value of 89.06%, material and language experts provide an assessment with an average percentage value of 89.06%, and practitioners provide an assessment with an average percentage value of 91.26 %, so that the average value of experts and practitioners is 88.08% with very decent product qualifications. The results of distributing questionnaires to students and teachers showed positive responses, in which the eight aspects assessed received an average percentage score of 95.47%. Learning media based on an Articulate Storyline containing local wisdom values is very feasible to support learning activities in class.